Analisis Sistem Pengendalian Internal Pembelian Bahan Baku Pada PT. Inalum - Rapat Piter Sony Hutauruk; Daniel Collyn; Rika Surianto Zalukhu (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2026)
This study aims to analyze the implementation of the internal control system for raw material purchasing at PT Indonesia Asahan Aluminium (INALUM). Internal control in the raw material purchasing process plays an important role in maintaining the effectiveness of company operations, minimizing the risk of errors and fraud, and ensuring the continuity of the production process. This study employed a qualitative approach with a descriptive method. Research data were obtained through observation, interviews, and documentation. Interviews were conducted with parties directly involved in the raw material procurement process, namely the Material Management Section and the Procurement Section. In addition, this study utilized supporting documents such as Standard Operating Procedures (SOP), business process documents, and company reports. The results indicate that the internal control system for raw material purchasing at PT INALUM has been implemented properly and systematically. The raw material procurement process is carried out through several stages, including the preparation of Purchase Requisition (PR), tender process, technical and business evaluation, negotiation, issuance of Purchase Order (PO), contract preparation, goods receipt, and payment. The company has also implemented segregation of duties, authorization systems, access restrictions, and the use of SAP and Ipro systems to support inventory control and raw material procurement processes. Furthermore, the company applies a risk mitigation strategy through Ad Hoc transactions to address raw material supply constraints under certain conditions. Based on the evaluation results, the internal control system for raw material purchasing at PT INALUM is in accordance with internal control principles and is capable of supporting the effectiveness and efficiency of the company’s raw material procurement process.